Menurunkan Kecemasan Sosial melalui Pemaknaan Kisah Hidup - Idei Khurnia Swasti; Wisjnu Martani (Faculty of Psychology, Universitas Gadjah Mada, 2013)
Negative self beliefs during social interaction and previous unpleasant social experiences increase level of social anxiety. This condition also leads person to form narrative tone about helplessness. This research aim is to apply Narrative Therapy for exploring experiences and other life stories from a highly anxious person to decrease his/her level of anxiety. The research participant (subject Y, female, 21 years old) fits the participant’s inclusive criteria, using Skala Kecemasan Sosial-Revisi (SKS-R). Y joins 8 sessions of individual therapy setting. SKS-R is given before and after therapy, and also in the follow up sessions. SKS-R score shows decrease in Y’s level of social anxiety from 226 (very high anxiety) to 112 (very low anxiety) and the low scores remain stable in two follow up sessions. Meanwhile, her safety behaviors frequency, which is observed using Observasi Perilaku Aman (OPA), shows unstable score per session. Narrative analysis on conversation transcript and Diari Pelaporan Diri (DPD) show narrative tone transformation. Before therapy, it is dominated by helplessness. After therapy, it is changed to empowerment and self esteem to fight against anxiety. Negative imagery of “Miss Panic” and “Miss Sensitive” is deleted. The conclusion is Narrative Therapy can decrease Y’s level of social anxiety. Further research can support Narrative Therapy reliability in different setting. Keywords: narrative therapy, social anxiety, narrative analysis